"Feeling Like I'm Slow Because I'm in This Class": Secondary School Contexts and the Identification and Construction of Struggling Readers. Issue 4 (4th July 2016) - Learned, Julie E.
Abstract: Despite increasing concern about the number of U.S. youths who experience reading difficulty, relatively little research has examined how or why adolescents' literacy skills vary across school spaces. During this school year—long study, I shadowed eight ninth graders identified as struggling readers across content area classes and compared their experiences with those of similar peers who were not labeled as such. I conducted 425 hours of observations, 64 semistructured interviews, and ongoing open‐ended ethnographic interviews, and I collected assessment scores, school records, and classroom artifacts. Analysis showed that students' and teachers' interactions with particular school contexts not only identified reading difficulty but also constructed "struggling readers" regardless, sometimes, of students' skilled, engaged reading. Contributing to deficit positioning were institutional contexts that conflated reading difficulty with behavioral problems. However, among classroom contexts in which youths experienced disciplinary literacy instruction situated in trusting and caring relationships, the young people tended to demonstrate proficient or improving reading and express positive feelings about themselves, their teachers, and their classes. Findings have implications for not only the reconceptualization of adolescent reading difficulty but also the reorganization of secondary literacy programs.